2009
DOI: 10.1172/jci38307
|View full text |Cite
|
Sign up to set email alerts
|

The impact of malaria parasitism: from corpuscles to communities

Abstract: Malaria continues to exert a tremendous health burden on human populations, reflecting astonishingly successful adaptations of the causative Plasmodium parasites. We discuss here how this burden has driven the natural selection of numerous polymorphisms in the genes encoding hemoglobin and other erythrocyte proteins and some effectors of immunity. Plasmodium falciparum, the most deadly parasite species in humans, displays a vigorous system of antigen variation to counter host defenses and families of functiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
57
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 64 publications
(58 citation statements)
references
References 123 publications
1
57
0
Order By: Relevance
“…1 The recent evidence of emerging resistance to artemisinin derivatives, including ACTs, in southeast Asia raises serious concern that such parasite populations may spread toward Africa, mirroring parasite resistance to chloroquine, 2 sulfadoxine, and pyrimethamine. 3 Recently, mutations in the PF3D7_1343700 kelch propeller (K13-propeller) domain were shown to be useful markers of delayed parasite clearance in surveillance for artemisinin resistance in southeast Asia.…”
Section: Introductionmentioning
confidence: 99%
“…1 The recent evidence of emerging resistance to artemisinin derivatives, including ACTs, in southeast Asia raises serious concern that such parasite populations may spread toward Africa, mirroring parasite resistance to chloroquine, 2 sulfadoxine, and pyrimethamine. 3 Recently, mutations in the PF3D7_1343700 kelch propeller (K13-propeller) domain were shown to be useful markers of delayed parasite clearance in surveillance for artemisinin resistance in southeast Asia.…”
Section: Introductionmentioning
confidence: 99%
“…Molecular-epidemiological studies have identified at least six independent origins of CQR in different regions of the world (23). These origins are distinguished by codon mutations and flanking polymorphisms of pfcrt, the transporter-encoding gene responsible for CQR (24,25).…”
mentioning
confidence: 99%
“…Anemia continues to exert tremendous burdens to human health. [1][2][3][4] Thus, a considerable effort has been made to develop new therapies for the treatment of anemia. Although the focus in the treatment of anemia has been on growth factors (eg, erythropoietin [EPO]), derivation of hematopoietic cells from human embryonic stem cells and induced pluripotent stem cells are considered a worthwhile endeavor in the areas of transfusion therapies.…”
mentioning
confidence: 99%